Facilitating outcomes: multi-stakeholder processes for influencing policy change on urban agriculture in selected West African and South Asian cities - Amerasinghe, Priyanie H.; Cofie, Olufunke O.; Larbi, Theophilus Otchere; Drechsel, Pay (International Water Management Institute, 2013)
The Multi-stakeholder Policy Formulation and Action Planning approach was applied in the context of a multi-city study to influence and/or change policies that govern urban agriculture practices in three African and two Asian countries. Although the approach was successful and resulted in remarkable outcomes, it showed space for improvement to facilitate its application. The study also showed that there are significant regional differences in how best to achieve policy change, which require careful attention in order to achieve the highest returns on investment in the facilitation of impact pathways.